Recognition and management of acute kidney injury in the International Society of Nephrology 0by25 Global Snapshot: a multinational cross-sectional study. Issue 10032 (14th May 2016) - Mehta, Ravindra L; Burdmann, Emmanuel A; Cerdá, Jorge; Feehally, John; Finkelstein, Fredric; García-García, Guillermo; Godin, Melanie; Jha, Vivekanand; Lameire, Norbert H; Levin, Nathan W; Lewington, Andrew; Lombardi, Raúl; et al.
Summary: Background: Epidemiological data for acute kidney injury are scarce, especially in low-income countries (LICs) and lower-middle-income countries (LMICs). We aimed to assess regional differences in acute kidney injury recognition, management, and outcomes. Methods: In this multinational cross-sectional study, 322 physicians from 289 centres in 72 countries collected prospective data for paediatric and adult patients with confirmed acute kidney injury in hospital and non-hospital settings who met criteria for acute kidney injury. Signs and symptoms at presentation, comorbidities, risk factors for acute kidney injury, and process-of-care data were obtained at the start of acute kidney injury, and need for dialysis, renal recovery, and mortality recorded at 7 days, and at hospital discharge or death, whichever came earlier. We classified countries into high-income countries (HICs), upper-middle-income countries (UMICs), and combined LICs and LMICs (LLMICs) according to their 2014 gross national income per person. Findings: Between Sept 29 and Dec 7, 2014, data were collected from 4018 patients. 2337 (58%) patients developed community-acquired acute kidney injury, with 889 (80%) of 1118 patients in LLMICs, 815 (51%) of 1594 in UMICs, and 663 (51%) of 1241 in HICs (for HICs vs UMICs p=0.33; p<0.0001 for all other comparisons). Hypotension (1615 [40%] patients) and dehydration (1536 [38%] patients) were the most common causes of acute kidney injury. Dehydration was the most frequent cause of acute kidney injury in LLMICs (526 [46%] of 1153 vs 518 [32%] of 1605 in UMICs vs 492 [39%] of 1260 in HICs) and hypotension in HICs (564 [45%] of 1260 vs 611 [38%%] of 1605 in UMICs vs 440 [38%] of 1153 LLMICs). Mortality at 7 days was 423 (11%) of 3855, and was higher in LLMICs (129 [12%] of 1076) than in HICs (125 [10%] of 1230) and UMICs (169 [11%] of 1549). Interpretation: We identified common aetiological factors across all countries, which might be amenable to a standardised approach for early recognition and treatment of acute kidney injury. Study limitations include a small number of patients from outpatient settings and LICs, potentially under-representing the true burden of acute kidney injury in these areas. Additional strategies are needed to raise awareness of acute kidney injury in community health-care settings, especially in LICs. Funding: International Society of Nephrology.